Association between Direction Patterns of Palatal Rugae and Thumbprints: Implications for Forensic Identification - Setiadi, Desyani; Syukriani, Yoni Fuadah; Supian, Sudradjat; Oscandar, Fahmi; Malinda, Yuti; Nugraha, Alhana (Journal of Dentistry Indonesia, 2019)
Palatal rugae have been proven to be useful as a means of individual identification. As there are no antemortem data about palatal rugae, they have to be connected with other indicators, such as fingerprints with available antemortem data. Objectives: To assess the association of the direction patterns of palatal rugae prints and thumbprints in the Deutero-Malay sub-race to improve forensic identification. Methods: Palatal rugae intraoral photos and thumbprints scans were from 193 Deutero-Malay individuals aged between 18–25 years (170 female, 23 male). ImageJ and Adobe software was used to identify direction patterns of the palatal rugae and thumbprints. Results: An antero-posterior direction was the most common direction pattern among right (64.17%) and left (49.26%) palatal rugae and right (58.12%) and left (56.02%) thumbprints. An association with small effect size was found between first right palatal rugae and right thumbprint (p-value = 0.024; Cramer’s V = 0.181) and with medium effect size between second left palatal rugae and left thumbprint (p-value = 0.000; Cramer’s V = 0.332). Conclusion: There is a significant association between the direction patterns of palatal rugae and thumbprints. This finding may lead to the development of a new effective technique in forensic odontology identification.